158P Role of iron metabolism in the immunosuppression mediated by myeloid cells in glioblastoma patients. (15th December 2019) - Magri, S; Pinton, L; Masetto, E; Cassandro, S; Pozzuoli, A; Belluzzi, E; Puppa, A Della; Mandruzzato, S
Abstract: Background: Glioblastoma multiforme (GBM) is one of the most malignant primary brain tumor and is known to create an immunosuppressive microenvironment that hampers the efficacy of therapies. We demonstrated that GBM microenvironment is infiltrated with a large proportion of bone marrow-derived macrophages (BMDMs) that possess a strong immune suppressive activity. Following 5-aminolevulinic acid (5-ALA) administration to patients before surgery, BMDMs show the highest protoporphyrin IX (PPIX) fluorescence emission, compared to immune and non-immune cells. Since PPIX is the precursor of heme we wondered if the presence of this metabolite could be the consequence of an altered iron metabolism in BMDMs, and if this pathway could be linked to their immunosuppressive activity. Methods: GBM tissues were dissociated and subjected to immunomagnetic or FACS sorting for the separation of BMDMs. The expression of HMOX1, the gene coding for heme oxygenase-1 (HO-1) which is a central enzyme in the iron pathway, was analyzed by RT-PCR. BMDM immune suppressive activity was evaluated as the ability to suppress the proliferation of T lymphocytes also in the presence of HO-1 inhibitors. In order to optimize the experimental conditions, immunosuppressive macrophages derived from M-CSF treated monocytes from healthy donors were set up. Another in vitro model of immunosuppressive cells, bone marrow derived-myeloid derived suppressor cells (BM-MDSCs), was tested. Results: HMOX1 expression was found to be upregulated in BMDMs compared to other cells. The treatment of BMDMs with a HO-1 inhibitor was able to restore T cells proliferation in immune suppressive assays. The recovery of immunosuppression following treatment with the inhibitor has also been demonstrated in macrophages and in BM-MDSCs. Conclusion: Our results show that the connection between iron metabolism and immune response could be exploited from a therapeutic point of view. In particular, HO-1 plays a role in BMDM-induced immunosuppression and could represent a new target to relieve the immunosuppressive microenvironment present in GBM patients. Legal entity responsible for the study: University of Padua. Funding: AIRC. Disclosure: All authors have declared no conflicts of interest.